The Janus‐like role of neuraminidase isoenzymes in inflammation. Issue 5 (1st April 2022) - Howlader, Md. Amran; Demina, Ekaterina P.; Samarani, Suzanne; Guo, Tianlin; Caillon, Antoine; Ahmad, Ali; Pshezhetsky, Alexey V.; Cairo, Christopher W.
Abstract: The processes of activation, extravasation, and migration of immune cells to a site are early and essential steps in the induction of an acute inflammatory response. These events are an essential part of the inflammatory cascade, which involves multiple regulatory steps. Using a murine air pouch model of inflammation with LPS as an inflammation inducer, we demonstrate that isoenzymes of the neuraminidase family (NEU1, 3, and 4) play essential roles in these processes by acting as positive or negative regulators of leukocyte infiltration. In genetically knocked‐out (KO) mice for different NEU genes ( Neu1  KO, Neu3  KO, Neu4  KO, and Neu3 / 4 double KO mice) with LPS‐induced air pouch inflammation, leukocytes at the site of inflammation were counted, and the inflamed tissue was analyzed using immunohistochemistry. Our data show that leukocyte recruitment was decreased in NEU1‐ and NEU3‐deficient mice, while it was increased in NEU4‐deficient animals. Consistent with these results, systemic as well as pouch exudate levels of pro‐inflammatory cytokines were reduced in Neu1 and increased in Neu4  KO mice. Pharmacological inhibitors specific for NEU1, NEU3, and NEU4 isoforms also affected leukocyte recruitment. Together our data demonstrate that NEU isoenzymes have distinct—and even opposing—effects on leukocyte recruitment, and therefore warrant further investigation to determine their mechanisms and importance as regulators of the inflammatory cascade.